KEY FACTORS INFLUENCING THE SUCCESS OF GENERIC PHARMACEUTICAL LAUNCHES IN SOUTH AFRICA - Naidoo, Kiasha (My University, 2011)
Changes in the pharmaceutical industry as a result of recent changes to the legislation, aimed at the affordability and access of medicines to South Africans, together with the large number of innovative products losing patent, have resulted in an increasingly competitive generic pharmaceutical market. The objective of the research was to identify the factors that contributed to the successful launch of generic products in South Africa as well as the factors that were responsible for ensuring the growth of generic post launch. The research identifies that in order to be more competitive, the main factors that need to be taken into consideration include competitive pricing vs the innovator, being the first to market, having an aggressive sales and marketing campaign, as well as leveraging re-imbursement by healthcare funders and medical aid switching. The main factors found to contribute to the growth of the products following launch are stock availability and effective distribution, leveraging re-imbursement and relationships with funders, sales force enthusiasm and the price of the generic relative to the innovator. By taking these factors into consideration, the research has identified some of the most successfully launched generic products as Adco-Simvastatin, Prexum, Adco-Amoclav BD, Cilift, Adco-Zolpidem and Rolab-Zopiclone.
MBA - WBS
Keywords: Generic medicines; Pharmaceuticals, Generic